PERGESERAN PARADIGMA LITERASI GENERATIF DI SEKOLAH DASAR: KAJIAN PUSTAKA TENTANG PERAN GEN-AI SEBAGAI MITRA METAKOGNITIF DALAM PEMBELAJARAN MEMBACA DAN MENULIS - Putri Rusnadi, Riska; Izza, Nur; Dewi, Ramlah; A. Arif, Tarman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid advancement of generative artificial intelligence (Gen-AI) has inaugurated a new era in elementary education, particularly within the domain of reading and writing literacy. This literature review aims to analyze the paradigm shift toward generative literacy in elementary schools and to critically examine how Gen-AI can function not merely as an automation tool but as a metacognitive partner that actively supports students in monitoring, planning, and evaluating their own literacy processes. A narrative review methodology was applied to 25 peer-reviewed articles published between 2023 and 2026, sourced from Scopus, Google Scholar, and nationally accredited Indonesian journals (Sinta). Three principal findings emerged: first, Gen-AI compels a redefinition of elementary literacy to encompass critical competencies for engaging with machine-generated text; second, when pedagogically scaffolded, Gen-AI can stimulate metacognitive functions in young learners through dialogic scaffolding, reflective feedback, and adaptive cognitive support; and third, effective implementation demands that teachers transform into designers of metacognitive experiences and ethical guardians of AI use. The practical implication of this review is the urgent need for pedagogical frameworks that position Gen-AI as an instrument of critical thinking rather than a substitute for children's cognitive processes.